The performance and bacterial community shifts in an anaerobic-aerobic process treating purified terephthalic acid wastewater under influent composition variations and ambient temperatures. (10th December 2020) - Ma, Kaili; Li, Xiangkun; Bao, Linlin; Li, Xiaoling; Cui, Yanrui
Abstract: Anaerobic-aerobic process is an efficient way to treat purified terephthalic acid (PTA) wastewater. In this study, the effect of changing feed composition on the performance of a combined upflow anaerobic fluidized bed (UAFB) and sequencing batch reactor (SBR) was investigated under ambient conditions (15–25 °C). The 187 days' operation was divided into 4 stages by consecutively elevating the loading rate of terephthalic acid (TA), p-toluic acid, benzoic acid and acetic acid. Results revealed that almost all iso-phthalic acid, benzoic acid and acetic acid could be completely removed in the UAFB reactor, while only about 35% p-toluic acid was degraded in the UAFB reactor. Nevertheless, over 97.0% average COD removal efficiency could be achieved after the consecutive aerobic treatment. Furthermore, the load elevation of easily biodegradable organics might enhance the operational stability together with a less diverse bacterial community in anaerobic system. The microbial analysis elucidated a large amount of versatile aromatic degraders including Syntrophorhabdus, Syntrophus and Syntrophobacteraceae were observed in UAFB reactor, but they did not show clear correlation with any specific pollutant. Meanwhile, the growth of Thauera and Rhodobacteraceae in SBR reactor were stimulated by p-toluic acid load elevation, and both of them showed strong positive correlation with p-toluic acid degradation. Overall, this study provides a comprehensive insight into the organics degradation characteristics and bacterial profiles of UAFB-SBR process treating complex industrial wastewater at ambient temperatures. Graphical abstract: Image 1 Highlights: UAFB-SBR process had good resistance to composition variations of PTA wastewater. Over 97% COD reduction was achieved in UAFB-SBR process at ambient condition. Load elevation of easily biodegradable organics could enhance overall performance. Prevailed bacterial groups promoting organics degradation were identified.